Bilinguals Produce Pitch Range Differently in Their Two Languages to Convey Social Meaning. (December 2022) - Passoni, Elisa; de Leeuw, Esther; Levon, Erez
We investigated whether expression of social meaning operationalized as individual gender identitity and politeness moderated pitch range in the two languages of female and male Japanese-English sequential bilinguals. The bilinguals were resident in either London (UK) or Tokyo (Japan) and read sentences to imagined addressees who varied in formality and sex. Results indicated significant differences in the pitch range of the two languages of the bilinguals, and this was confirmed for female and male bilinguals in London and Tokyo, with the language differences being more extreme in the London bilinguals than in the Tokyo bilinguals. Interestingly, self-attribution of masculine gender traits patterned with within-language variation in the English pitch level of the female bilinguals, whereas self-attribution of feminine gender traits patterned with within-language variation in the English pitch level of the male bilinguals. In addition, female and male bilinguals significantly varied their pitch range in Japanese, but not in English, as a function of the imagined addressees. Findings confirmed that bilinguals produce pitch range differently in their languages and suggest that expression of social meaning may affect pitch range of the two languages of female and male bilinguals differently.